Higher-order thinking skills based on Marzano taxonomy in basic biology I course - Metri Dian Insani; Novida Pratiwi; M. Muhardjito (University of Muhammadiyah Malang, 2019)
This research was aimed at profiling student’s thinking skills in dealing with Higher-Order Thinking Skills (HOTS) questions based on Marzano taxonomy by referring to 13 indicators. This pre-experimental research employed pretest-posttest design. The indicators included were comparison, classification, deductive reasoning, inductive reasoning, error analysis, construction, analysis perspective, abstraction, decision making, investigation, problem solving, inquiry experiment, and innovation finding. The instrument used was a 13-essay question (r-Pearson= 0.79 and Cronbach alpha = 0.68). The data gained from 98 students of Natural Science Education was then analyzed using paired t-test. The results showed the significant different between pre-test and posttest (sig. <0.01). As many as four HOTS indicators (i.e. deductive reasoning, error analysis, construction, and abstraction) were categorized as low level. Meanwhile, the eighth HOTS indicators were categorized as moderate level, namely: comparison, inductive reasoning, analysis perspective, decision making, investigation, solving problem, inquiry experiment, and innovative finding. In addition, the classification indicator was considered in high level in the end of the course. It can be concluded that, in general, students’ HOTS are still in moderate level. Thus, the proper strategies should be designed to improve this condition into the optimal level.